Carbon Dioxide (CO2) Separation Study Using Chemically Activated Serpentine as an Adsorbent - Dhedia, Muhammad Fannka; Mahidin, Mahidin; Husin, Husni; Hisbullah, Hisbullah; Razali, Nasrullah; Reza, Alvan Ade; Hadi, Abdul (Jurnal Rekayasa Kimia & Lingkungan, 2024)
The increase in carbon emissions resulting from industrial activities has become a major concern for environmental and climate conditions. Carbon Capture and Storage (CCS) represents a significant effort to mitigate the CO2 problem. Aceh Province possesses a potential distribution of serpentine, which may serve as an effective material for CCS applications. This study evaluates the effects of gas flow rate, particle size, sorbent weight, and pressure on CO2 adsorption using chemically activated serpentine. The activation process involved hydrochloric acid (HCl) at three concentrations: 8%, 9%, and 10%, with particle sizes of 50 mesh, 100 mesh, and 150 mesh. Activation was conducted at room temperature with an acid-to-serpentine ratio of 10:1 for 30 minutes. Adsorption tests were performed at ambient temperature under pressures of 2, 3, and 4 bar, with adsorption times of 30, 60, and 120 minutes. Results indicate that activated serpentine treated with 9% HCl and a particle size of 150 mesh achieved the highest performance, demonstrating an adsorption efficiency of 33.01% and an adsorption capacity of 82.22% (0.0488 g CO2/g adsorbent) at a pressure of 2 bar. Both the Langmuir and Freundlich isotherm models closely fit the data (R = 1). This study concludes that HCl activation significantly enhances the capacity and efficiency of serpentine as a CO2 adsorbent.